2020
DOI: 10.46827/ejoe.v5i2.3381
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Interactivity in Online Learning – Towards the Achievement of High-Quality Online Learning Outcomes

Abstract: Online learning is different from face-to-face contact learning. The former is technology-mediated and often accused of lacking the interaction the learners would have when learning together in contact sessions. However, the richness of online learning is flexibility, which allows learning to take place anytime from anywhere. Online learning through the utilisation of digital learning platforms may provide rich learning experiences. The Covid-19 pandemic prompted most institutions of higher learning to move to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…This study has several implications for academic research. First, it builds upon the work of Çakiroğlu and Kahyar, 9 Swan, 10 and Rugube et al 11 by utilizing a learning analytics approach to empirically analyze the interactivity attributes that influence learning outcomes, based on Moore’s 1 interactivity model and Garrison et al’s 13 CoI framework theory.…”
Section: Conclusion Implications Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has several implications for academic research. First, it builds upon the work of Çakiroğlu and Kahyar, 9 Swan, 10 and Rugube et al 11 by utilizing a learning analytics approach to empirically analyze the interactivity attributes that influence learning outcomes, based on Moore’s 1 interactivity model and Garrison et al’s 13 CoI framework theory.…”
Section: Conclusion Implications Limitations and Future Workmentioning
confidence: 99%
“…2,7,8 However, it has been noted that the effect of interactivity on learning performance or satisfaction in online learning has not been fully explored in the literature. To justify this gap, several relevant studies have suggested the importance of interaction in online learning, including the work of Çakiroglu and Kahyar, 9 Swan, 10 and Rugube et al 11 In this study, we aim to fill this gap by exploring the effect of interactivity on student achievement by extracting student interaction data from CANVAS, an online learning system.…”
Section: Introductionmentioning
confidence: 99%
“…The term "interactive" denotes the way how two or more people connect and influence each other through communication (such as in the case of students to teachers, or their fellow students). In the height of the pandemic where online learning became the major instructional modality, providing various collaborative and interactive learning opportunities is crucial to delivering a rich learning experience to students (Rugube et al, 2020). Meanwhile, the term "buzz" may refer to a noun that manifests an ambiance (either in residential face-to-face or in a virtual ecosystem) characterized by enthusiasm and enjoyable activities.…”
Section: Interventionmentioning
confidence: 99%
“…Besides, because of the spread of COVID-19, face-to-face schooling was actively interrupted. This resulted in a significant shift to the online learning model, as students and teachers remained at home for their own protection (Rugube et al, 2020;Brief, P., 2020). Using digital tools to enhance group communication and collaboration has been shown to increase student involvement in group activities.…”
Section: Collaborative Learning (Cl) and Computer Supported Collabora...mentioning
confidence: 99%